2017
DOI: 10.1101/207498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Association Study of Body Fat Distribution identifies Novel Adiposity Loci and Sex-Specific Genetic Effects

Abstract: Body mass and body fat composition are of clinical interest due to their links to cardiovascular- and metabolic diseases. Fat stored in the trunk has been suggested as more pathogenic compared to fat stored in other compartments of the body. In this study, we performed genome-wide association studies (GWAS) for the proportion of body fat distributed to the arms, legs and trunk estimated from segmental bio-electrical impedance analysis (sBIA) for 362,499 individuals from the UK Biobank. A total of 97 loci, were… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…The selective regions detected by XP-EHH showed a similar pattern to those found by F ST , XP-CLR, and log 2 (π ratio ). Overall, 40, 67, and 43 overlapping regions were detected by XP-EHH and F ST , XP-CLR, and log 2 (π ratio ), respectively (Supplementary Data [44][45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selective regions detected by XP-EHH showed a similar pattern to those found by F ST , XP-CLR, and log 2 (π ratio ). Overall, 40, 67, and 43 overlapping regions were detected by XP-EHH and F ST , XP-CLR, and log 2 (π ratio ), respectively (Supplementary Data [44][45].…”
Section: Resultsmentioning
confidence: 99%
“…As the main lipid storage depot, adipocytes play a crucial role in buffering the daily influx of dietary fat into circulation. In humans, body fat distribution is of clinical interest because of its links to multiple metabolic diseases 45 . Previous studies reported that fat stored in the trunk was more pathogenic than that stored in other compartments, and the accumulation of adipose tissue in the upper body (abdominal region) was more pathogenic than that in the lower body (gluteofemoral region) 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have confirmed the obesity-type 2 diabetes discordant genetic effects and the link to fat distribution and lipid metabolism, and genes that may represent targets for precision medicine approaches have been highlighted [82]. However, both fat distribution and the pathogenic effects by the adipose tissues are known to differ between sexes [83,84], and future studies stratifying by sex are therefore needed to increase the precision in prevention and treatment strategies for obesity [85].…”
Section: Genetic Subtyping In Obesity and Metabolismmentioning
confidence: 99%
“…We follow this discussion by talking about the role of the oestrogen receptors (ERs) in adipose tissues. We provide a brief discussion on what was learned through genome-wide association studies (GWAS) regarding how oestrogenregulated genes influence sex differences in body fat distribution [10]. We expand our discussion on the role sex plays in determining adipose tissue function by discussing the role sex chromosomes have in influencing adiposity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…We provide a brief discussion on what was learned through genome-wide association studies (GWAS) regarding how oestrogenregulated genes influence sex differences in body fat distribution [10]. We expand our discussion on the role sex plays in determining adipose tissue function by discussing the role sex chromosomes have in influencing adiposity [10,11]. Oestrogens also influence adipose tissue lineage and epigenetics as additional methods they impact metabolism.…”
Section: Introductionmentioning
confidence: 99%